Water-induced switching of beta-structure to polyproline II conformation in the 4s-aminoproline polypeptide via H-bond rearrangement - Sonar, Mahesh V.; Ganesh, Krishna N. (Organic Letters, 2010)
4S-Aminoproline polypeptide 2 forms unusual beta-structure in trifluoroethanol that switches to the polyproline II (PPII) form in aqueous medium. while 4R-aminoproline peptide 1 retains PPII form in both solvents. This first instance of a polyproline derivative showing a beta-structure is attributed to competitive pH-dependent (4-NH3+/NH2) stereoelectronic effect (4R vs 4S) and the overriding importance of stercospecific intra/intermolecular H-bonding in (2,4)-cis-4S-aminoproline in contrast to (2,4)-trans-4R-aminoproline oligomers.